2016
DOI: 10.1051/matecconf/20166600062
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary framework for corporate real estate sustainable management

Abstract: Abstract. The global warming issue has motivated corporations to go green in their business operations including transforming from conventional real estate to green features real estate. However green CRE is more complex to manage due to a building's significant impact on environmental, social and economic aspects. Thus the need to have a best practice guide or framework as reference is crucial. Unfortunately, no best practice guidelines on CRE management have been found to be sufficient as much uncertainty st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…On a further gloomy note, Azlan et al found in 2009 that the majority of building industry people have lack of experience, and a low level of understanding on the green building rating system. This finding coincided with Fauzi et al's (2016) where evidence showed that not only were end users still unaware on the green building concept, even the key players in green building development also displayed poor knowledge on green building. Aliagha et al (2013) commented that Malaysia's green tax incentives are inherent but not significantly attractive, coupled with lack of public awareness, database and information technology, and professional knowledge.…”
Section: Green Building Still At a Very Early Stage Of Awarenesssupporting
confidence: 72%
“…On a further gloomy note, Azlan et al found in 2009 that the majority of building industry people have lack of experience, and a low level of understanding on the green building rating system. This finding coincided with Fauzi et al's (2016) where evidence showed that not only were end users still unaware on the green building concept, even the key players in green building development also displayed poor knowledge on green building. Aliagha et al (2013) commented that Malaysia's green tax incentives are inherent but not significantly attractive, coupled with lack of public awareness, database and information technology, and professional knowledge.…”
Section: Green Building Still At a Very Early Stage Of Awarenesssupporting
confidence: 72%
“…CRESM is a management of sustainable/green CRE owned by non-real estate companies. CRESM is a practice of corporate real estate management that embeds sustainable triple-bottom-line principles of environmental, social and economic (Fauzi et al, 2016). CRESM is also known as sustainable corporate real estate management (Ziemba et al, 2015).…”
Section: Interpretation Of Green Cre and Cresmmentioning
confidence: 99%
“…Because this topic is new, not many studies have been conducted in the past, particularly in Malaysia. In Finland, Masalskyte et al (2014) discovered twenty elements of CRESM, while Fauzi et al (2016) through a literature review, identified fourteen elements of CRESM that divided into three main elements of economic, environmental and social as similar to UNEP (2014). In a study conducted in the Netherlands, Sinke (2015) discovered eight components of CRESM.…”
Section: Elements Of Cresmmentioning
confidence: 99%
“…Furthermore, literature reviews have been executed to identify which factors are important to make offices more sustainable [e.g. [7][8][9][10]. But what is not clear yet, is which expectations CRE managers have when they decide about implementing certain sustainable measures.…”
Section: Introductionmentioning
confidence: 99%